2021
DOI: 10.1177/23259671211023099
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Anterolateral Ligament Reconstruction or Lateral Extra-articular Tenodesis Combined With Primary ACL Reconstruction: A Systematic Review With Meta-analysis

Abstract: Background: Residual rotational instability after isolated anterior cruciate ligament reconstruction (ACLR) has been a challenge for many years. Anterolateral extra-articular procedures (AEAPs), including anterolateral ligament reconstruction (ALLR) or lateral extra-articular tenodesis (LET), are performed as a surgical option for additional rotational stability, but clear evidence for their usefulness is lacking. Purpose: To conduct a systematic review and meta-analysis of the literature regarding the efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 69 publications
0
35
0
3
Order By: Relevance
“…Specifically, Rezende et al 41 demonstrated in a systematic review that combined reconstruction is associated with significantly better knee stability based on not only the pivot-shift test (risk ratio, 0.95 [95% CI, 0.91-0.99]; P = .02) but also the Lachman test (risk ratio, 0.93 [95% CI, 0.88-0.98]; P = .01). Similarly, Na et al, 37 in a more recent systematic review and meta-analysis, demonstrated that the proportion of patients with Lachman grade 2 or 3 was significantly lower in the combined reconstruction group than in the isolated ACLR group (odds ratio, 0.42 [95% CI, 0.20-0.89]; P = .02; I 2 = 0%).…”
Section: Discussionmentioning
confidence: 83%
“…Specifically, Rezende et al 41 demonstrated in a systematic review that combined reconstruction is associated with significantly better knee stability based on not only the pivot-shift test (risk ratio, 0.95 [95% CI, 0.91-0.99]; P = .02) but also the Lachman test (risk ratio, 0.93 [95% CI, 0.88-0.98]; P = .01). Similarly, Na et al, 37 in a more recent systematic review and meta-analysis, demonstrated that the proportion of patients with Lachman grade 2 or 3 was significantly lower in the combined reconstruction group than in the isolated ACLR group (odds ratio, 0.42 [95% CI, 0.20-0.89]; P = .02; I 2 = 0%).…”
Section: Discussionmentioning
confidence: 83%
“…Na et al performed a systematic literature review and concluded that 'the general control of rotation and the protective effect on the graft' is more important than the specific procedure used to augment the ACL reconstruction. 22 Procedures reconstructing other components of the ALC, such as the ALL of the knee, have also been shown to be effective in improving control of the pivot shift. 23 This may be the case even if the anterolateral procedure is added as second procedure in patients who present with persistent rotatory instability following previous ACL reconstruction whether perform anatomically, 24 or a non-anatomically.…”
Section: Discussionmentioning
confidence: 99%
“…Na et al . performed a systematic literature review and concluded that ‘the general control of rotation and the protective effect on the graft’ is more important than the specific procedure used to augment the ACL reconstruction 22 . Procedures reconstructing other components of the ALC, such as the ALL of the knee, have also been shown to be effective in improving control of the pivot shift 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Concerns regarding addition of this procedure include the risk of over-constraint and later degenerative joint disease, the lack of definitive diagnostics methods to guide decision-making and a few anatomical studies examining the anterolateral pediatric knee. 73 , 74 One recent cadaveric study has demonstrated that the anterolateral complex is inconsistent, ill-defined, and underdeveloped in children highlighting the need for further research. 75 …”
Section: Aeapsmentioning
confidence: 99%